Les enfants terribles - Faribault, Bernard (Assurances, 1986)
Article 2564 C.C. was the subject of two recent and apparently contradictory judgments of the Provincial Court on the question of the rights of an assured to be defended by his insurer, when his liability is sought for damages caused intentionally to a third party by his children. One court held that article 2564 C.C. does not allow putting into effect the disculpatory clause found in article 1054 C.C. in similar circumstances. Me Faribault explains that even if the legislator had wanted to effect a sweeping reform by drafting article 2564 C.C. as he did, he should not be seen as "having thrown out the baby with the bathwater".